2017
DOI: 10.1111/ajt.14161
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Protocol Biopsies to Identify Patients With De Novo Donor-Specific Antibody at High Risk for Allograft Loss

Abstract: De novo donor specific antibody (dnDSA) is associated with antibody mediated rejection (AMR) and allograft loss, yet the allograft histology associated with dnDSA remains unclear. The aim of this study was to examine the allograft histology associated with dnDSA in patients with serial surveillance biopsies. We retrospectively studied adult conventional solitary kidney transplant recipients from 10/2007–5/2014. DnDSA was new DSA with MFI >1000. The incidence of dnDSA was 7.0%(54/771) over mean follow-up of 4.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 22 publications
5
89
1
1
Order By: Relevance
“…[P = 0.004] for early ACR, and 41.0% vs 7.0% [P < 0.0001] for late ACR, respectively). Liver fibrosis developed in 81.4% (72.1% mild [stage 1-2], 9.3% advanced [stage [3][4]) of LSBT children, compared to 79.5% (64.1% mild, 15.4% advanced) in LT (P = 0.6), after a median post-transplant follow-up of 2.2 years and 2.4 years, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[P = 0.004] for early ACR, and 41.0% vs 7.0% [P < 0.0001] for late ACR, respectively). Liver fibrosis developed in 81.4% (72.1% mild [stage 1-2], 9.3% advanced [stage [3][4]) of LSBT children, compared to 79.5% (64.1% mild, 15.4% advanced) in LT (P = 0.6), after a median post-transplant follow-up of 2.2 years and 2.4 years, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The association between medication nonadherence and dnDSA has been well‐documented, but few studies have systematically examined the relationship between physician directed immunosuppression reduction for infectious disease reasons and subsequent development of dnDSA . A small cohort study of 19 patients with BK viremia showed that 79% developed de novo DSA with preemptive immunosuppression reduction .…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Previous work has shown that features of antibody-mediated rejection (glomerulitis and peritubular capillaritis) in the setting of BK nephropathy are predictors of graft loss. 29 The association between medication nonadherence and dnDSA has been well-documented, 15,18,19,[30][31][32] but few studies have systematically examined the relationship between physician directed immunosuppression reduction for infectious disease reasons and subsequent development of dnDSA. 33 immunosuppression reduction.…”
Section: Discussionmentioning
confidence: 99%
“… Recipients with post‐transplant DSA: recipients showing post‐transplant DSA, either de novo DSA or pre‐transplant DSA that were maintained after transplant. The definition of de novo DSA was any DSA identified at least a week after transplant that was absent at any time prior to transplant (each recipient had at least one pre‐transplant SAB test) Recipients with no post‐transplant DSA: recipients who did not show DSA pre‐transplant or in any of the post‐transplant studies. …”
Section: Methodsmentioning
confidence: 99%